EPIDENDRA, the taxonomic databases by Jardín Botánico Lankester - Pupulin, Franco (Universidad de Costa Rica, 2015)
t may seem somehow out of line to present a new system of botanical databases in the context of a meeting on orchid conservation, for two main rea- sons. Even though botanists have been rather slow in upgrading to the use of electronic databases (with some early controversy regarding the desirability of the application of electronic data processing methods to taxonomic problems as a whole, see i.e. Shetler 1974), the dissemination of plant information via the web has grown steadily in recent years.